Food handlers’ knowledge and practices and the relationship with appropriate sanitation hygiene scores in Malang City - Aulia, Nurul; Budiningsari, Dwi; Lestari, Lily Arsanti (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2024)
Background: Food hygiene and sanitation in catering services are affected by food handlers because they are the first to come in contact with food ingredients. This matter is essential to prevent food contamination. Objective: This study aimed to determine the relationship between food handlers’ knowledge and practices and appropriate sanitation hygiene scores in catering services in Malang City, East Java, Indonesia.Materials and Methods: Two hundred four food handlers and 24 catering services participated in this cross-sectional study. Knowledge data were collected through validated questionnaires filled out by subjects, and food handlers’ practices were obtained through observation with a checklist. Subjects who scored >70 were considered to have sufficient knowledge and practice. Good sanitation hygiene was collected through interviews and face-to-face observations and given a score to determine appropriate sanitation hygiene scores. c2 and Pearson correlation analyses were performed.Results: Subjects generally had sufficient knowledge (82.8%) but poor food handling practices (57.8%) because of less frequent and comprehensive training, and food handlers did not apply their knowledge in food processing. Only a quarter of catering services (6 of 24) were rated as having good sanitary hygiene. There was no relationship between food handlers’ knowledge and practices and appropriate sanitation hygiene scores in catering services (p = 0.925 and 0.2363, respectively).Conclusion: Food handlers generally have sufficient food safety knowledge but have poor practice categories, and sanitation hygiene scores are in the inappropriate category. There is no relationship between food handlers’ knowledge and practices and sanitation hygiene scores in catering services.Keywords: Knowledge; practice; food handlers; hygiene sanitation; catering services.